Georgian Hero of the Soviet Era Against the Universe: Science Fiction as a Nation’s Coping Mechanism - Keti Chartolani (Slovo, 2019)
To download this paper, please, click here. This paper analyses the process of constructing the national identity in the Soviet Georgian science fiction. Using the postcolonial approach, I argue that the genre provided Georgian writes with the unique possibility to imagine the future of Georgia, independent from the Russian oppression. The article concentrates on three strategies that serve this very goal: the first strategy entails placing Georgia in the centre of the future communist society; the second strategy entails transforming the historical rival of Russia, Western Europe and the United States of America, into Georgia’s arch-enemy; while the third strategy concentrates on the critique of the imperialist worldview. In all three cases, the narratives containing nationalistic sentiments still manage to stay within the borders of socialist realism.